2016
DOI: 10.1051/0004-6361/201628253
|View full text |Cite
|
Sign up to set email alerts
|

Search for associations containing young stars (SACY)

Abstract: Context. The young associations offer us one of the best opportunities to study the properties of young stellar and substellar objects and to directly image planets thanks to their proximity (<200 pc) and age (≈5−150 Myr). However, many previous works have been limited to identifying the brighter, more active members (≈1 M ) owing to photometric survey sensitivities limiting the detections of lower mass objects. Aims. We search the field of view of 542 previously identified members of the young associations to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 99 publications
2
50
0
Order By: Relevance
“…, and then by Torres et al (2006) and Lépine & Simon (2009). The membership was recently confirmed by Binks & Jeffries (2014, Riedel et al (2014), and Elliott et al (2016). Our LS and CLEAN analyses of ASAS time series revealed two possible rotation periods: P = 6.43 d and P = 1.22 d (see Fig.…”
Section: -2mass J04435686+3723033 (V 962 Per)supporting
confidence: 72%
See 3 more Smart Citations
“…, and then by Torres et al (2006) and Lépine & Simon (2009). The membership was recently confirmed by Binks & Jeffries (2014, Riedel et al (2014), and Elliott et al (2016). Our LS and CLEAN analyses of ASAS time series revealed two possible rotation periods: P = 6.43 d and P = 1.22 d (see Fig.…”
Section: -2mass J04435686+3723033 (V 962 Per)supporting
confidence: 72%
“…Based on 12 epochs of astrometric observations (where the observed separation ranges from 0.095 to 0.307 ), Janson et al (2014) estimated an orbital period of 30 yr. The membership of the β Pictoris association was first proposed by Zuckerman et al (2001), , then by Torres et al (2008) and confirmed by Binks & Jeffries (2014, and by Elliott et al (2016). Scholz et al (2007) measured a projected rotational velocity v sin i = 5.3 km s −1 .…”
Section: -2mass J01535076-1459503mentioning
confidence: 84%
See 2 more Smart Citations
“…The age of the HD 160934 system predicted by the models in Fig. 7 is between 15 Myr and 60 Myr, near the young estimates of the age of the AB Dor-MG. Age estimates of the AB Dor-MG range from 50−120 Myr (Malo et al 2013), 70 Myr (Zuckerman et al 2011), 70−120 Myr (Gagné et al 2014), 100−150 Myr (Elliott et al 2016), and 130−200 Myr (Bell et al 2015). It should be mentioned that the possibility that HD 160934 does not belong to the AB Dor-MG cannot be ruled out.…”
Section: Comparison With Modelsmentioning
confidence: 99%